Tourism in the Sharia Frame: A Study on the Relationship of Tourism and Religion in Yogyakarta - Thoyyib Alfath; Destita Mutiara; Muhammad Rasyid Ridho (Fakultas Agama Islam Universitas Muhammadiyah Yogyakarta, 2022)
Indonesia is one of the countries with a majority Muslim population in the world and has the potential to develop the halal industry, namely sharia tourism. The Special Region of Yogyakarta is one of the regions that has its cultural wealth and nature by developing this potential as an increase in the regional economy, as well as increasing the halal score of the Indonesian industry for the world. Local governments made various efforts to improve services for tourists interested in sharia tourism, such as ACES (Access, Communication, Environment, and Services). This study uses a qualitative method by interviewing parties involved in the concept and implementation of sharia tourism in Yogyakarta (Yogyakarta Tourism Office and Yogyakarta Indonesian Ulema Council) and also uses literature obtained from websites and books as the data used. The results found in this research are that halal or sharia tourism in Yogyakarta has been said to be advanced with the concept offered, following the Grand Design of Sharia Tourism Development by the National Committee for Sharia Economics and Finance. However, what is of concern to implementing the sharia tourism concept both in Yogyakarta and other areas is the extent to which the sharia concept is implemented correctly, namely by the religious foundation (Qur'an and Hadith).